2004
DOI: 10.1074/jbc.m312141200
|View full text |Cite
|
Sign up to set email alerts
|

Selective Roles for Tumor Necrosis Factor α-converting Enzyme/ADAM17 in the Shedding of the Epidermal Growth Factor Receptor Ligand Family

Abstract: Epidermal growth factor (EGF) family ligands are derived by proteolytic cleavage of the ectodomains of integral membrane precursors. Previously, we established that tumor necrosis factor ␣-converting enzyme (TACE/ ADAM17) is a physiologic transforming growth factor-␣ (TGF-␣) sheddase, and we also demonstrated enhanced shedding of amphiregulin (AR) and heparin-binding (HB)-EGF upon restoration of TACE activity in TACEdeficient EC-2 fibroblasts. Here we extended these results by showing that purified soluble TAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 81 publications
6
106
1
Order By: Relevance
“…Extensive data show that various members of the ADAM (a disintegrin and metalloproteinase) family of zinc-dependent cell surface enzymes that includes ADAM17 (TNFα converting enzyme, TACE), are responsible for the release of all EGFR ligands, including AREG, in culture [34][35][36][37]. Moreover, even juxtacrine activation of EGFR via direct cell-to-cell contact may require the ADAM17-mediated processing of EGFR agonists [38], although such contactdependent activation is almost certainly irrelevant during mammary development, since epithelial and stromal cells are generally separated by a basement membrane.…”
Section: Epithelial Adam17 Is Required For Mammary Developmentmentioning
confidence: 99%
“…Extensive data show that various members of the ADAM (a disintegrin and metalloproteinase) family of zinc-dependent cell surface enzymes that includes ADAM17 (TNFα converting enzyme, TACE), are responsible for the release of all EGFR ligands, including AREG, in culture [34][35][36][37]. Moreover, even juxtacrine activation of EGFR via direct cell-to-cell contact may require the ADAM17-mediated processing of EGFR agonists [38], although such contactdependent activation is almost certainly irrelevant during mammary development, since epithelial and stromal cells are generally separated by a basement membrane.…”
Section: Epithelial Adam17 Is Required For Mammary Developmentmentioning
confidence: 99%
“…In contrast, NegGM, a structurally similar compound without metalloprotease inhibitory activity, did not inhibit TNF-a-induced phosphorylation of ERK1/2 as well as phosphorylation of NF-kB ( Figure 6A). It has recently been demonstrated that shedding of EGFR ligands is mediated by some members of the ADAMs family of metalloproteases, especially ADAM17 (Hinkle et al, 2004;Sahin et al, 2004). We therefore examined the effect of TAPI-1, an ADAMs inihibitor.…”
Section: Effects Of Metalloprotease Inhibitors On Tnf-a-induced Cellumentioning
confidence: 99%
“…Similarly, the TACE cleavage site in the growth hormone receptor also resides in a structurally similar JM region (Baumann and Frank, 2002). It appears that both stalk length and sequence are critical determinants of TACE cleavage (Hinkle et al, 2004). Further experimentation is needed to determine whether TACE is indeed responsible for JM cleavage of IFNaR2, and to determine the actual cleavage site.…”
Section: Discussionmentioning
confidence: 99%